Access to healthcare in Chile - Olavarría Gambi, Mauricio (Acta Bioethica, 2005)
Chile presents a remarkable lessening of its poverty; indicators show that people’s healthcare conditions are close to those of the developed countries. This paper analyses the healthcare conditions of people with the lowest incomes, if they have access to medical and dental care when they are sick, if this care is readily obtained or with delay or when it is already late, and if they get coverage from the healthcare protective systems.